Twist1-Haploinsufficiency Selectively Enhances the Osteoskeletal Capacity of Mesoderm-Derived Parietal Bone Through Downregulation of Fgf23 - Quarto, Natalina; Shailendra, Siny; Meyer, Nathaniel P.; Menon, Siddharth; Renda, Andrea; Longaker, Michael T. (Frontiers in Physiology, 2018)
Craniofacial development is a program exquisitely orchestrated by tissue contributions and regulation of genes expression. The basic helix–loop–helix (bHLH) transcription factor Twist1 expressed in the skeletal mesenchyme is a key regulator of craniofacial development playing an important role during osteoskeletogenesis. This study investigates the postnatal impact of Twist1 haploinsufficiency on the osteoskeletal ability and regeneration on two calvarial bones arising from tissues of different embryonic origin: the neural crest-derived frontal and the mesoderm-derived parietal bones. We show that Twist1 haplonsufficiency as well Twist1-sh-mediated silencing selectively enhanced osteogenic and tissue regeneration ability of mesoderm-derived bones. Transcriptomic profiling, gain-and loss-of-function experiments revealed that Twist1 haplonsufficiency triggers its selective activity on mesoderm-derived bone through a sharp downregulation of the bone-derived hormone Fgf23 that is upregulated exclusively in wild-type parietal bone